Study on Topological Modification Method Considering Torsional Deformation of Double Planetary Gear Shafts - Chen Xuehui; Pu Mingchun; Gao Ting; Zhang Xudong; Fang Weidong; Li Hao; Liu Wei (Jixie chuandong)
In order to solve the problems of eccentric load of planetary gear train and large impact of gear teeth meshing caused by torsional deformation of double planetary gear shafts under load, a topological modification method considering torsional deformation of double planetary gear shaft is proposed. The causes of torsional deformation of the double planetary gear shaft and its influence on the load sharing performance of the gear train are analyzed. Based on the multi body gear bearing contact analysis (PLTCA) and the gear bearing contact analysis (LTCA), the bearing transmission error and the tooth surface load distribution coefficient under the deformation are solved; the optimization intelligent algorithm is used to solve the optimal solution of the modification parameters under the condition of the maximum modification amount of the tooth surface; the simulation results show that the proposed method can effectively reduce the unit length load of the tooth surface and the amplitude of the transmission error. The unit length load of the first and second planetary tooth surfaces is reduced by 33.58% and 21.35% respectively, and the amplitude of the transmission error is reduced by 77.74%; the experimental verification is carried out on the reducer load test-bed, and the experimental results are consistent with the simulation results. The wear condition of the planetary gear surface is greatly improved, the problem of eccentric load of NGWN planetary gear train is better solved, and the transmission accuracy and service life of the equipment are improved.